Fiscal Reform Agenda: Getting Ready for the Bumpy Ride Ahead - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2004)
The paper traces the roots of the present fiscal problem and concludes that it is largely attributable to the deterioration of the national governments revenue effort. On the other hand, because the government relied heavily on across-the-board budget cuts in order to maintain some semblance of fiscal control in the face of a persistent decline in revenue performance, investments in physical and human capital suffered the brunt of the adjustment. At the same time, the study points out that it is not enough to focus on the fiscal position of the national government and highlights the need to look at the complete fiscal picture by examining more closely the consolidated public sector deficit. The fiscal deficit of nonfinancial public sector has been rising steeply (from 0.6% of GDP in 1996 to over 7% of GDP in 2003) largely on account of government-owned and/or controlled corporations (GOCCs). In turn, outstanding debt of the nonfinancial public sector rose persistently from 75.4 percent of GDP in 1996 to 105.0 percent as of end of September 2003. The study then proceeds to outline the key elements of a fiscal reform agenda: tax policy and tax administration reform, public expenditure management reform, and GOCC reform. It points out that the burden of the adjustment should rest on the revenue side. At the same time, any further attempt to cut government expenditure in the aggregate is likely to be counterproductive. This does not mean, however, that reforms are not needed on the expenditure side. With or without a fiscal problem, reforms in public expenditure management are essential in ensuring that government gets the biggest bang out of every peso that it spends. In this regard, minimizing waste and curbing corruption should be on top of the agenda. The paper then spells out in some detail the needed reforms in each of the three areas. A big part of the paper is devoted to an evaluation of the many new tax measures that have been proposed to date.
Keywords: 330; fiscal deficit; tax effort; public expenditure management; GOCC reform; consolidated public sector; Finanzpolitik; Öffentliche Finanzen; Gemischtwirtschaftliches Unternehmen; Finanzreform; Steuerreform; Philippinen